2022
DOI: 10.1088/1741-2552/ac63e9
|View full text |Cite
|
Sign up to set email alerts
|

Phase-amplitude coupling between low-frequency scalp EEG and high-frequency intracranial EEG during working memory task

Abstract: Objective. Revealing the relationship between simultaneous scalp electroencephalography (EEG) and intracranial electroencephalography (iEEG) is of great importance for both neuroscientific research and translational applications. However, whether prominent iEEG features in the high-gamma band can be reflected by scalp EEG is largely unknown. To address this, we investigated the phase-amplitude coupling (PAC) phenomenon between the low-frequency band of scalp EEG and the high-gamma band of iEEG. Approach. We an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Recent studies have indicated that HPC is a critical region involved in WM maintenance, especially when dealing with an increasing cognitive load. [10][11][12][13] While AMY has traditionally been thought to be related only to emotions, recent findings indicate that it also participates in non-emotional WM memory. The multi-dimensional response characteristics of this region, such as blood oxygen level-dependent (BOLD) responses and sustained neural activity are found to be dependent on memory loads.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that HPC is a critical region involved in WM maintenance, especially when dealing with an increasing cognitive load. [10][11][12][13] While AMY has traditionally been thought to be related only to emotions, recent findings indicate that it also participates in non-emotional WM memory. The multi-dimensional response characteristics of this region, such as blood oxygen level-dependent (BOLD) responses and sustained neural activity are found to be dependent on memory loads.…”
Section: Introductionmentioning
confidence: 99%